PROMOSI KESEHATAN PENTINGNYA GIZI SEIMBANG DAN VAKSIN DI ERA PANDEMI - Riezky Faisal Nugroho; Erika Martining Wardani (Universitas Haji Sumatera Utara, 2022)
During the COVID-19 pandemic, people are encouraged to adopt a healthy lifestyle. Several ways can be done to prevent transmission, including the consumption of balanced nutrition and vaccines. Health promotion is important. The purpose of the service is to promote health about the importance of balanced nutrition and vaccines in the pandemic era in Surabaya. The method in this service is by providing health promotion webinars. Participants in this service were 66 participants. Before and after the provision of health promotion in the form of education, an evaluation was carried out by distributing questionnaires via a google form link containing pre and post test questions. The results of this community service show that the majority of participants aged 30-39 years (63%), participants who know about balanced nutrition have a pre-test result of 24.2%, and post-test results are obtained as much as 78.8%, participants who know about vaccines get pre-test results. test 21.2%, and post test 81.8%, while the statistical test results obtained p = 0.001, meaning that there is a significant difference between public knowledge before and after being given health promotion through webinars. It is important to give health promotion as a preventive effort about balanced nutrition and vaccines on a regular basis so that people know and apply the knowledge that has been obtained so that people stay healthy in the midst of this covid-19 pandemic